Culturally Responsive Special Education - Gerzel-Short, Lydia; Jerae, Kelly; Hovey, Katrina A.; Hsiao, Yun‐Ju; Wei, Yan (Advances in educational marketing, administration, and leadership book series, 2023)
Keywords: dept.sed

Preparing culturally responsive teachers: a systematic review - Miller, Rhonda D.; Gerzel-Short, Lydia; Kelly, Jerae H.; Uphold, Nicole; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan (Multicultural Learning and Teaching, 2023)
As the world continues to ponder issues of equity and diversity, U.S. public schools face an expanding demographic divide between teachers and students. While diverse groups of public school students show an increase in population, the teaching workforce in the U.S. remains overwhelmingly White. The purpose of this systematic review is to examine how preservice teachers (PST) are being prepared to be culturally responsive. A total of 26 studies published between 2006 and 2020 were reviewed. The results indicate that PSTs’ learning experiences are varied and tend to be stand-alone approaches focused on changing the attitudes and beliefs of PSTs. Findings also bring to light the vagueness of terminology used in the research to define cultural groups of students, the conspicuous absence of studies related to LGBTQ+ populations, and the lack of study replications. Implications for future research are discussed.
Keywords: culturally responsive; dept.sed; diversity; peer-reviewed; pre-service teacher; teacher education; teacher preparation

Developing simulation materials to support teacher anti-racist and anti-ableist practice during iep meetings: Supporting general educator collaborative practice - Perouse-Harvey, Ebony (Advocating and Empowering Diverse Families of Students With Disabilities Through Meaningful Engagement, 2023)
Research demonstrates discriminatory and inequitable practices related to students identified with (disabilities). Inequitable practices and discrimination reveal the necessity of collaboration and advocacy as an integral part of the pedagogy of professional development for members of the IEP team. Providing pre-service (or preparing) teachers simulated experiences of individualized education program (IEP) meetings can support PSTs understanding of how ableism and racism can manifest in schools, develop skills in collaborating with families, and begin to develop advocacy practices that support students that are marginalized at the intersection of their race and ability status. This chapter focuses on how to develop materials that leverage critical theoretical frameworks, provide learning experiences that mirror teacher practice in schools, and provide authentic representations of families of color to develop PSTs collaborative and advocacy practices. © 2023 by IGI Global. All rights reserved.
Keywords: dept.sed

Increasing outcomes: principles of practice to increase writing outcomes for deaf/hard of hearing students with additional disabilities - Weir, Joan; Dostal, Hannah M. (Strategies for Promoting Independence and Literacy for Deaf Learners With Disabilities, 2023)
The ability to write clearly and effectively is an important communication skill that is necessary for school and employment, as it is often the best way to disseminate information and ideas. Both unrecorded sign and speech are ephemeral, but writing allows the author to share an experience or idea...
Keywords: dept.sed